Successful Management of a Giant Splenic Cyst during Pregnancy: A Rare Case - Siati, Abderrahim; Ghaddou, Youssef; Sair, Khalid; Dehayni, Mohamed (Clinical Journal of Obstetrics and Gynecology, 2024)
Background: Maternal splenic cyst during pregnancy appears to be a rare pathology whose treatment is not codified. The most feared complication is rupture during pregnancy. It occurs in 60% of cases in the third trimester of pregnancy, leading to significant maternal-fetal morbidity and mortality. Case report: We describe the successful management of a 24-year-old patient, G1P0, with a history of a recurrent splenic cyst. She presented with a giant splenic cyst measuring 28 cm in diameter at 30 weeks of amenorrhea. A cesarean section was performed at 37 weeks gestation. A splenectomy was performed on day 21 postpartum. Conclusion: The incidence of splenic cysts is extremely rare during pregnancy. The diagnosis must be made as early as possible to undertake appropriate treatment before the appearance of maternal-fetal complications.